Investigation of voluntary feed intake and behavior of lambs fed different roughages by camera monitoring - Esad Sami Polat; Behiç Coşkun; Emel Gürbüz; Tahir Balevi; İbrahim Çivlik (Eurasian Journal of Veterinary Sciences)
For a better understanding of the dynamics of animals' behavior an observation, recording and validation method has been improved which clarifies the differentiation in roughage composition by means of eating kinetics This method makes it possible to continuously and closely monitor a unique animal's behavior by recording its activities individually and through its group with minimal disturbance to animals. In this method, a camera monitoring system supported by computer was assembled, in indoors recording for 24 hours a day from the top ol animals. Penned young sheep (n=6, trealments=4) were fed with (our of completely different fiber sources: Barley Straw. Corn Silage, Alfalfa Hay and Sugar Beet Pulp ad libitum, 6 times a day in 4 hour meal intervals and eating behavior ol animals were investigated on. BS group animals spent the shortest time for eating 157,2 min with less number of eating bouts 14 4 limes and consumed lowest dry matter (%1.08 of liveweight). AH group animals responded to their base diet very well that longer lime of eating occurred (218 mm) in highly repeated terms of 19.7 times a day and dry mailer intake was %3 3 of liveweight CS was consumed with the longest time spent for eating (219.8 min). number ol eating bouts was not as frequent as AH group with 18.4 times and intake was %2.32 of liveweight. SBP dry matter intake was %2.38 ol liveweight. Animals consumed SBP in shorter bouts (189.7 min) than CS and AH, but the number of eating bouts has been significantly higher (22.7 times/day), which means that SBP animals preferred shorter but more frequent meals. The heaviest leed consumption was occurred at sunsel. In controlled indoor conditions at individual pens, animals spent most of their time resting (%73).